RELAKS DENGAN FEAR OF MISSING OUT (FOMO) DALAM PERSPEKTIF GELASSENHEIT MARTIN HEIDEGGER - Rex Firenze Tonta (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
The focus of this paper discusses the Fear of Missing Out (FoMO) phenomenon, which is a condition of anxiety when users miss the latest information, do not update other people's activities in their absence. These conditions can encourage users to experience internet addiction and spend a lot of time on the internet, in order to get a feeling of being involved and joining. Dasein condition that dissolves in everyday life in a digital world like that will be reflected in Martin Heidegger's thoughts about technology and human relations with it, specifically Gestell and Gelassenheit. The purpose of this paper is to offer a metaphysically based attitude (so it's not just a pragmatic attitude), when dealing with gadgets or mobile phones, Gelassenheit. The method used in this paper is qualitative, with a phenomenological approach. In this article, I also take a lot of inspiration from F. Budi Hardiman's book Aku Klik Maka Aku Ada. The findings in this paper, Heidegger's thoughts about technology are still relevant today. It must be admitted that technology is indeed very beneficial for human life, it is also a revelation of history, users are engrossed and busy thinking calculatively and at home in the digital world. So Heidegger's offer of the Gelassenheit attitude, namely relaxing towards tools provides important and deep inspiration for users.